Alumni Capital: University Alumni Relations strategy - D. I. Zemtsov; I. S. Khukalenko (Высшее образование в России, 2023)
The purpose of this study is to describe the strategies of interaction with alumni and suggest directions for their inclusion in the managerial arsenal of the central administration of the university. The Far Eastern Federal University, relatively recently created on the basis of four independent universities, three of which were strongly industry-oriented, provides rich material for research on strategies of interaction with alumni that have developed in its various structural divisions. At the same time, most of these strategies are not initiated by the central administration, and the biggest part of them even is out of its view. Strategies for interaction with alumni arise as forms of reproduction, increment and conversion of the social capital of alumni, leaders of the academic community and several departments of the university. The university appears to researchers as a kind of “exchange office”, in which there is a constant movement of different types of capital, the main of which is social and its subspecies – alumni capital.